2018
DOI: 10.7150/ijbs.26335
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA485-3p negatively regulates the transcriptional co-repressor CtBP1 to control the oncogenic process in osteosarcoma cells

Abstract: Carboxyl-terminal binding protein 1 (CtBP1), a well-known transcriptional co-repressor, is highly expressed in a number of cancer types. However, it is still absent in osteosarcoma cells. Here, we found that CtBP1, but not CtBP2, is overexpressed in invasive osteosarcoma tissues and cells. The overexpressed CtBP1 in turn represses its downstream targets, such as the pro-apoptotic regulators Bax, Bim and p53 upregulated modulator of apoptosis (PUMA), cell adhesion molecule E-cadherin, and the cell cycle regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…miR-485-3p functions as a tumor-suppressor in different types of cancers and signaling pathways. For example, low expression of miR-485-3p was observed in osteosarcoma that negatively regulate CtBP1, a transcription co-repressor, which can associate with epigenetic enzymes for regulating downstream genes like Bax, Bim, E-cadherin, PUMA, p16, p21, and PTEN (22). Decreased expression of miR-485-3p was clarifi ed to be age-dependent in lung adenocarcinoma (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-485-3p functions as a tumor-suppressor in different types of cancers and signaling pathways. For example, low expression of miR-485-3p was observed in osteosarcoma that negatively regulate CtBP1, a transcription co-repressor, which can associate with epigenetic enzymes for regulating downstream genes like Bax, Bim, E-cadherin, PUMA, p16, p21, and PTEN (22). Decreased expression of miR-485-3p was clarifi ed to be age-dependent in lung adenocarcinoma (24).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences demonstrate that miR-485-3p can act as an oncogene in gastric cancer (16), hepatocellular carcinoma (17,18), prostate cancer (19,20), and lymphoma (21). In contrast, studies showed that miR-485-3p can act as a tumor-suppressor in osteosarcoma (22), NSCLC lung cancer (23,24), glioblastoma (25) and breast cancer (26). However, its role in initiation and progression of colorectal cancer has remained disputed.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that miRNAs may be involved in the regulation of CtBPs. For example, Du and colleagues found that miR-485-3p negatively regulates the expression of CtBP1 by directly binding to its 3'-untranslated region (3'-UTR) [46]. Deng and colleagues identified that miR-137 can repress the expression of CtBP1 by binding to its 3'-UTR [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-485-3p was demonstrated to directly interact with the 3′-UTR of CtBP1, while the expression of miR-485-3p was associated with the DNA methylation of CpG islands in its promoter. When treating with 5′-AZA, miR-485-3p was upregulated to inhibit OS cell development by reducing CtBP1 expression [69]. High methylation levels in the CpG sites of miR-7 promoter were decreased by treating 5′-AZA, thus promoting miR-7 expression in OS cells.…”
Section: Osteosarcomamentioning
confidence: 99%